BENTUK DAN PROSES BANTUAN LUAR NEGERI AMERIKA SERIKAT KE ISRAEL TAHUN 2017-2020 - Emilio Ramos Markus (2022)
The United States and Israel are two countries that have one of the most unique relationships. Relations between the two countries can be traced back since the formation of the state of Israel. Over time, conflicts after conflicts occurred in the Middle East involving Israel, not infrequently a number of these conflicts endangered Israel's existence in the Middle East. The unique relationship between the two countries makes the United States consider Israel as their main ally in the Middle East. So it is important for the United States to help Israel maintain their survival in this conflict-prone area. One of the United States' efforts is through their foreign aid to Israel. Through this research, the author will try to explain what forms and how the process of US foreign aid to Israel in 2017-2020. This research is a qualitative research using descriptive research methods. Research data was collected through document-based and internet-based methods, with primary data sourced from reports on US foreign aid to Israel in 2017 2020 published directly by the United States government. The results of the study show that during 2017-2020, the United States has provided significant foreign assistance in the military and non-military fields to Israel and the process of granting it has also been going well.